The Drug Reimbursement Decision-Making System in Iran - Yousefi, Hesam; Ansaripour, Amir; A. Uyl-de Groot, Carin; Steenhoek, Adri; K. Redekop, William (International Pharmacy Acta, 2018)
Background: Previous studies of health policies in Iran have not focused exclusively on the drug reimbursement process. Objective: The aim of this study was to describe the entire drug reimbursement process and the stakeholders, and discuss issues faced by policymakers. Methods: Review of documents describing the administrative rules and directives of stakeholders, supplemented by published statistics and interviews with experts and policymakers. Results: Iran has a systematic process for the assessment, appraisal, and judgment of drug reimbursements. The two most important organizations in this process are the Food and Drug Organization, which considers clinical effectiveness, safety, and economic issues, and the Supreme Council of Health Insurance, which considers various criteria, including budget impact and cost-effectiveness. Ultimately, the Iranian Cabinet approves a drug and recommends its use to all health insurance organizations. Reimbursed drugs account for about 53.5% of all available drugs and 77.3% of drug expenditures. Despite its strengths, the system faces various issues, including conflicting stakeholder aims, lengthy decision-making duration, limited access to decision-making details, and rigidity in the assessment process. Conclusions: The Iranian drug reimbursement system uses decision-making criteria and a structured approach similar to those in other countries. Important shortcomings in the system include out-of-pocket contributions due to lengthy decision making, lack of transparency, and conflicting interests among stakeholders. Iranian policymakers should consider a number of ways to remedy these problems, such as case studies of individual drugs and closer examination of experiences in other countries.